Chemical and physical data of tar balls and biological characteristics of rafting organisms from the landfall event on tropical sandy beaches (~8S) of northeastern coast of Brazil in 2022 - Davy Barbosa Bérgamo; Nykon Craveiro; Karine Matos Magalhães; Gilvan Takeshi Yogui; Eliete Zanardi-Lamardo; Lino Angel Valcarcel Rojas; José Souto Rosa Filho (PANGAEA, 2023)
As the demand for production and transportation of marine oil increases worldwide, oil spills from a variety of sources have occurred repeatedly in recent decades. These spills lead to the formation of tar balls, the final stage of residual oil, which, as other floating materials, can act as substrates for colonization by marine organisms, including goose barnacles and polychaeta. The dispersal of these tar balls in the ocean gives rise to several ecological consequences and societal impacts, such as chemical contamination, the introduction of non-indigenous species, loss of biodiversity and ecosystem services, and significant economic implications, particularly affecting coastal communities that depend on fishing and tourism. To comprehend the role of tar balls in coastal pollution and to develop effective tools for environmental monitoring and management, it is essential to employ biological and chemical methods of analysis. These datasets contain physical (length, width, volume, and weight) and chemical (aliphatic and polycyclic aromatic hydrocarbon analysis based on Wang et al., 1999 and Albaigés et al., 2015) data of the interior and surface of 37 tar balls. Additionally, it includes biological data (taxonomic identification, capitulum length, width, weight, and maturation stage) of 413 rafting organisms found attached to tar balls. The manual collection of tar balls colonized by these rafting organisms was conducted during the event of landfall on the tropical sandy beaches (~8S) of the northeastern coast of Brazil in August and September 2022 (Bérgamo et al., 2023). The analyses were performed at the Benthos Laboratory and the Organic Compounds in Coastal and Marine Ecosystems Laboratory, both part of the Department of Oceanography at the Federal University of Pernambuco, Brazil.